MULTIPLE INTELLIGENCES, CARA MENSTIMULASI SERTA IMPLEMENTASINYA DALAM PEMBELAJARAN (Forum Ilmu Sosial, 2011)
One of the implementations of Multiple Intelligences (MI) theory is to view all students intelligent in their own talents. This concept has replaced the concept of intelligence Quotient (IQ) which unconsciously has differentiated students to be intelligent and stupid. This concept, in the past, became one of the barriers for the â€œstupidâ€ students to get their education appropriately, and this was clearly to be in the contrary with the philosophy of Education for All (EFA), for every student, whatever their â€œintelligencesâ€ are, has his/her right to get the basic education. The advantage of the implementation of â€œMultiple Intelligencesâ€ concept on learning instruction is that this concept uses developmental approach, therefore it focuses more on the studentsâ€™ strengths to be developed; while the concept of â€œIntellectual Intelligenceâ€ still usesÂ  remedial approach, therefore it focuses more on the studentsâ€™ weaknesses to be remedied. This approach is also in the contrary with the learning principle of the Behaviorism which considers â€œrewardâ€ in higher priority than â€œpunishmentâ€ in learning process. This article discusses the concept of MI, how to stimulate it, and its implementation on learning instruction. Keywords: Multiple Intelligences, stimulate, implementation on learning instruction